PENGEMBANGAN E-COMIC MATEMATIKA BERBASIS TEKNOLOGI SEBAGAI SUPLEMEN PEMBELAJARAN PADA APLIKASI FUNGSI KUADRAT - Adeliyanti, Septi; Hobri, H; Suharto, S (Kadikma, 2018)
The purpose of this research was to produce a product to attract students’ interest in learning mathematics tha tested the validity, practicality, and effectiveness of using e-Comic based technology as a learning supplement to the application of quadratic functions. The development of technology is very rapid resulted in many students’ more interested in in using gadgets such as computer, laptops, handphone, and tablets rather than reading the textbook activities. This research was processed through the stages of 4D that is define, design, development, and disseminate. This research was conducted in SMP Negeri 7 Jember which involved 32 students’ of class 9B. The result of the research show that the development media is valid according to the material expert and the media expert with the percentage of the archieved value 95,3% from validator I, 89% from validator II, and validator III gives 96% value. Effective media with learning test reasult followed 32 students’ in this research show 81,25% complete. Quetionnaire showed a percentage of a 94% from student for practicality. Keywords: e-Comic mathematics, learning suplement